Price transmission in Nigerian food security crop markets - Hatzenbuehler, Patrick L.; Abbott, Philip C.; Abdoulaye, Tahirou (Wiley, 2017)
This paper comprehensively examines price transmission from world, neighbour country, and internal commercial hub markets to Nigerian urban markets, as well as from urban to rural markets within the country, for seven key food security crops (maize, millet, sorghum, rice, cassava, yams and cowpeas). There are three key findings: (i) tradability matters for price transmission, but tradability varies across crops and regions. The strongest international linkages are with neighbouring countries. Rice price transmission is high across all markets, while coarse grain price correspondence is low with world prices but high with neighbour country market prices; (ii) our results imply that local conditions matter for price transmission, and are relatively more important than trade for some crops (e.g. yams, cassava) than others (e.g. imported rice, maize); (iii) larger than expected long-run price transmission parameters in world and neighbour countries for rice and coarse grains suggest that, in these select markets, there are either large transactions costs or quality premiums that vary systematically with border prices, and/or mark-ups captured by traders with market power.